1996
DOI: 10.1007/bf02415582
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of molecular forms of iodine from the gaseous phase by protective paint coatings

Abstract: In the designs of new units for nuclear power plants (of the type NP-500. NP-600) ensure safety in the event of accidents on the basis of passive heat removal from the hermetically sealed zone by providing for an accident pond. The heat removal system is also intended to keep radioactive products, including iodine, within the containment vessel.Up to 99% of the iodine in the coolant of a VVI~R reactor is in the form of an iodide. In the presence of the oxygen in the air the iodide ion is oxidized to molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The absorption varied with the partial pressure to the power 0.59. This contrasts with the linear dependence found by Aleksandrov et al [1996] for the absorption of iodine by epoxy paints. Sukawa et al [1987] found that nylon would absorb about 1.7 grams of molecular iodine per gram of nylon from a 0.1 M aqueous solution.…”
Section: Polyamide Resincontrasting
confidence: 89%
“…The absorption varied with the partial pressure to the power 0.59. This contrasts with the linear dependence found by Aleksandrov et al [1996] for the absorption of iodine by epoxy paints. Sukawa et al [1987] found that nylon would absorb about 1.7 grams of molecular iodine per gram of nylon from a 0.1 M aqueous solution.…”
Section: Polyamide Resincontrasting
confidence: 89%